Successful Treatment of Autoimmune Hemolytic Anemia with Sirolimus after Allogeneic Hematopoietic Stem Cell Transplantation: A Case Report - Hyun Jin Park; Jung Yoon Choi; Kyung Taek Hong; Bo Kyung Kim; Hyoung Jin Kang (The Korean Society of Pediatric Hematology-Oncology, 2023)
Autoimmune hemolytic anemia (AIHA) is a common complication after hematopoietic stem cell transplantation (HSCT). Although post-HSCT AIHA is associated with poor prognosis and is more resistant to treatment than primary AIHA, the standard treatment has not yet been determined. We report a case of post-HSCT AIHA, which occurred 9 years after unrelated donor bone marrow transplantation for acute biphenotypic leukemia. Steroid treatment was initially effective but prolonged steroid usage, due to recurrent relapses, caused avascular necrosis. Although rituximab was unsuccessful in preventing relapses, sirolimus was effective in allowing the discontinuation of steroid treatment and sustaining transfusion-free status. Sirolimus, previously reported to be effective in pediatric post-HSCT AIHA and AIHA after solid organ transplantation, may be effective in adult post-HSCT AIHA as well.